(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Sandhivata (osteoarthritis) is a disease of old age people and usually hampering the working hours and quality of life in number of peoples worldwide. We have found this Ayurvedic treatment very effective in the management of this disease. Hence a time bound clinical research work was framed for objective assessment of the improvement. The study was performed on osteoarthritis of knee joint over fifty patients. The diagnostic and assessment criteria were mainly clinical, along with visual analogue scale for pain and Algo Functional Lequesne Index (Knee) to assess the severity of knee osteoarthritis. The symptoms included were pain, swelling, stiffness, tenderness, joint crepitus and decreased movement. The drugs Sanjeevani vati, Dashamula kwatha, Punarnava mandura and Yava kshara were given for thirty days, with one follow up at fifteen days. There was a drop out of four patients during the trial. The pain (2.18±0.72), stiffness (1.93±0.72) and restriction of movements (2.28±0.81) are the three major complaints followed by crepitus (1.82±0.72), tenderness (1.43±1.10) and swelling (1.29±1.01). The initial score of severity of the disease was 9.75+4.16; which was reduced to 6.20+4.33 after 15 days and it was 3.49+1.16 at the end of the trial, this also gives a highly significant ‘t’ and ‘p’ score i.e. 15.11 and p< 0.001 respectively. So, the effect of combined therapy was evaluated moderate to high in reducing severity of disease. Some patient even told that they have felt relief in symptoms just on the 2nd day after starting the treatment.